2021
DOI: 10.1007/s00382-021-05764-2
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian approach to exploring the influence of climate variability modes on fire weather conditions and lightning-ignited wildfires

Abstract: Understanding the relationships between large-scale, low-frequency climate variability modes, fire weather conditions and lighting-ignited wildfires has implications for fire-weather prediction, fire management and conservation. This article proposes a Bayesian network framework for quantifying the influence of climate modes on fire weather conditions and occurrence of lightning-ignited wildfires. The main objectives are to describe and demonstrate a probabilistic framework for identifying and quantifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…The class of Bayesian networks used in this study is explained in an earlier paper (Bates et al, 2021) and so is only briefly described here. The approach, called sparse dynamic Bayesian networks (SDBNs), incorporates the temporal dimension by including lagged and non-lagged variables.…”
Section: Bayesian Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The class of Bayesian networks used in this study is explained in an earlier paper (Bates et al, 2021) and so is only briefly described here. The approach, called sparse dynamic Bayesian networks (SDBNs), incorporates the temporal dimension by including lagged and non-lagged variables.…”
Section: Bayesian Networkmentioning
confidence: 99%
“…The indices chosen to characterize these modes were Niño3.4 index (N34) for ENSO; dipole mode index (DMI) for IOD, tripole index (TPI) for IPO, an observation‐based index for SAM, and for QBO the mean zonal winds at 30 hPa (U30) and 50 hPa (U50) over Singapore. Further details on these indices are given in Bates et al (2021) and Table 2.…”
Section: Case Studymentioning
confidence: 99%
“…The study observed seasonal cycles and long-term patterns in lightning ignitions. Bates et al [138] used the Bayesian network as a framework to assess climate variability in lightning-induced wildfires, and unlike the lightning ignitions, the climate modes were allied to the fire weather conditions. Dorph et al's [139] study in Victoria, Australia, also indicated that lightning-caused wildfires are steered by weather conditions.…”
Section: Asia and Australiamentioning
confidence: 99%
“…The BNW can solve the uncertainty of evaluating wildfires by combining the prior conditional probability and the relationship between factors (Jiang et al, 2016;Albuquerque et al, 2017;Bates et al, 2021). However, the network complexity may be timeconsuming and storage-consuming of the model.…”
Section: Comparison Of Bwn Nb and Wnbmentioning
confidence: 99%